1999
DOI: 10.1295/polymj.31.550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain End Group–Substrate Interaction on Surface Molecular Motion of Polystyrene Ultrathin Films

Abstract: Surface molecular motions of monodisperse proton-terminated polystyrene (PS-H), monocarboxyl-terminated PS (PSCOOH) and dicarboxyl-terminated PS (a,w-PS(COOHh) ultrathin films were investigated on the basis of lateral force microscopic (LFM) measurement at 293 K, as a function of number-average molecular weight, M •. and chain end functionality. In the case of the PS-H thin films with M. = 19.7k and 40.4k spin-coated onto Si-wafer, the surface molecular motion was activated in a glass-rubber transition state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…They also reported that monodisperse polystyrene with molecular weight less than 30 000 is at the glass−rubber transition even at 293 K; , the T g depression of polydisperse polystyrene is greater than the monodisperse samples due to the chemistry of the chain ends: 35 the surface has chain end segregation as determined by secondary ion mass spectroscopy depth profiling, and polystyrene end-capped with a fluorinated group reduced T g more than the proton end-capped polymer . Thin, monodisperse polystyrenes terminated by proton and carboxylic acid group on a silane-treated silicon substrate show reduction of the degree of T g suppression seen in the free-standing films by a strong film−substrate interaction …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…They also reported that monodisperse polystyrene with molecular weight less than 30 000 is at the glass−rubber transition even at 293 K; , the T g depression of polydisperse polystyrene is greater than the monodisperse samples due to the chemistry of the chain ends: 35 the surface has chain end segregation as determined by secondary ion mass spectroscopy depth profiling, and polystyrene end-capped with a fluorinated group reduced T g more than the proton end-capped polymer . Thin, monodisperse polystyrenes terminated by proton and carboxylic acid group on a silane-treated silicon substrate show reduction of the degree of T g suppression seen in the free-standing films by a strong film−substrate interaction …”
Section: Introductionmentioning
confidence: 98%
“…32 In a related subject of thin film T g , an extensive investigation has been carried out on the surface T g by the group of Kajiyama and Takahara in the past several years. [33][34][35][36][37][38] Conclusions common to these papers are that the T g of the polymer surface is lower than the bulk, which is attributed to the segregation of the chain ends near the surface. Expectedly, this conclusion is the same as that obtained from free-standing thin films already described previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The author9–10 has investigated the surface morphology of carboxyl‐terminated polystyrene, PS‐COOH, on different substrates and concluded that the dewetting behavior of PS‐COOH on Si‐wafer substrate occurred upon annealing. Also, the adsorption of modified polymer onto solids from solution is not only of academic interest but is also a fundamental aspect of numerous applications such as electronic devices, coating, and lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…One surface investigated here, and in prior studies, ,, is SiO x , which is a hydrophilic surface. To create a more hydrophobic yet polar surface, a self-assembled monolayer (SAM) terminated with an amino group is deposited on SiO x . Our studies will show that a stronger matrix−substrate interaction is partly responsible for improved film stability on amine-terminated surfaces.…”
Section: Introductionmentioning
confidence: 99%